Persepsi Guru terhadap Integrasi Pendidikan Kebencanaan dalam Pembelajaran Geografi - Nurul Khotimah; Miftahul Ilmi (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to analyze teachers' views on the integration of disaster education into geography learning in senior high schools (SMA/MA) in Langsa City. This study used a quantitative descriptive method with a Likert-scale questionnaire completed by 20 teachers from nine schools. The four main indicators examined were knowledge, attitudes, learning practices, and school policy support for the implementation of disaster education. The study findings indicate that teachers have a high level of knowledge about disaster (89.46%) and also show a positive attitude towards the importance of disaster education (86%). School policies are also stated to be supportive (86%). However, the implementation of disaster learning practices is still moderate (56%), influenced by limited facilities, lack of direct student experience, and schools that are not accustomed to conducting routine mitigation activities. Qualitative findings confirm that regular simulations, curriculum integration, strengthening student understanding, and collaboration with external institutions are important steps to improve the effectiveness of disaster education in schools. Therefore, disaster education already has a strong conceptual basis and structural support, but needs to be improved in terms of field practice.